Invading the Occupied Niche: How a Parasitic Copepod of Introduced Oysters Can Expel a Congener From Native Mussels - Feis, Marieke E.; Gottschalck, Leo; Ruf, Lena C.; Theising, Franziska; Demann, Felicitas; Wegner, K. Mathias (Frontiers in Marine Science, 2022)
In species introductions, non-native species are often confronted with new niches occupied by more specialized natives, and for introduced parasites this conflict can be amplified because they also face novel hosts. Despite these obstacles, invasions of introduced parasites occur frequently, but the mechanisms that facilitate parasite invasion success are only rarely explored. Here, we investigated how the parasitic copepod Mytilicola orientalis, that recently spilled over from its principal host - the Pacific oyster Crassostrea gigas, managed to invade the niche of blue mussel Mytilus edulis intestines, which is densely occupied by its specialist congener, Mytilicola intestinalis. From field observations demonstrating invasion dynamics in nature, we designed a series of experiments addressing potential mechanisms facilitating a successful occupation of the new niche. As expected the specialist M. intestinalis can only infect mussel hosts, but displayed higher infection success there than M. orientalis in both principal host species combined. In the absence of direct competitive interactions M. orientalis compensated its lower infection success (1) by recurrent spill-over from its high-fitness reservoir oyster host, and (2) by active aggregation interference enhancing its own mating success while limiting that of M. intestinalis. The introduced parasite could thus avoid direct competition by changing its own epidemiology and indirectly decreasing the reproductive success of its competitor in the new host. Such mechanisms outside of direct competition have seldom been considered, but are crucial to understand invasion success, parasite host range and community assembly in the context of species introductions.